Expression of FGF23 in patients at different stages of chronic kidney diseases and its correction with left ventricular hypertrophy, PLSγ/calcineurin NFAT signaling pathway - ZHANG Yan; REN Rong; MA Yun; ZHANG Lei; MO Ying (Linchuang shenzangbing zazhi)
Objective To investigate the correlation of the expression of FGF23 with left ventricular hypertrophy in patients at different stages of chronic kidney diseases, and its effect on the signaling pathway for phospholipase Sγ(PLSγ)/calmodulin-activated T cell nuclear factor(NFAT). Methods The CKD patients, who visited the Fifth Affiliated Hospital of Xinjiang Medical University from October 2016 to September 2018, were screened. A total of 107 patients who met the criteria were divided into various groups at 2-5 diseases stages according to their glomerular filtration rates(GFR), and 30 healthy people served as the control. GFR, serum fibroblast growth factor 23(FGF23), cardiac structure and PLSγ/calcineurin NFAT signaling pathway were detected respectively, and the correlation of FGF23 with cardiac structure and its effect on PLSγ/calcineurin NFAT signaling pathway were analyzed. Results In an order of the healthy control group-stage CKD2 group-stage CKD3 group-stage CKD4 group-stage CKD5 group, the GFR levels of the patients decreased and the FGF23 level increased in turn, and there were significant differences in the two indicators between the two groups(P<0.01). With the increase of CKD stages of the patients, the levels of IVST, LVPWT, LVID, LVM and LVMI of the right ventricle increased in turn, and there were significant differences between the disease groups and the healthy control group(P<0.05). There were significant differences in IVST, LVPWT and LVM between the stage CKD 5 group and all the other groups(P<0.05). Spearman correlation analysis showed that serum FGF23 was positively correlated with LVID, IVS-R, LVPWT, LVM and LVMI in 107 patients with CKD, with a correlation coefficient of 0.256, 0.285, 0.274, 0.433 and 0.498; negatively correlated with E/A ratio, with r=-0.431; and, both calcineurin and phosphorylated NFAT(pNFAT) expressed in the serum in the CKD patients. Conclusions Serum FGF23 levels are prevalent in patients with stage 2-5 CKD, and significantly correlated with left ventricular hypertrophy. And elevated FGF23 levels may activate the PLSγ/calcineurin NFAT signaling pathway.